Pendapatan dan Efisiensi Teknis Usaha Tani Jernang (Daemonorops Draco) di Desa Lamban Sigatal Kecamatan Pauh Kabupaten Sarolangun Provinsi Jambi - Siti Abir Wulandari; Jonathan Tio Pande Simbolon (Universitas Batangahari Jambi, 2021)
The purpose of this research is to find out; (1) jernang farming activities in Lamban Sigatal Village, Pauh District, Sarolangun Regency, Jambi Province (2) analyzing production costs in jernang farming in Lamban Sigatal Village, Pauh District, Sarolangun Regency, Jambi Province (3) analyzing jernang farming income in Lamban Sigatal Village, Subdistrict Pauh, Sarolangun Regency, Jambi Province. This research was conducted in Lamban Sigatal Village, Pauh District, Sarolangun Regency, Jambi Province, this research was conducted in June 2021, with a total sample of 15 data used in the study. The analytical method used in this study was carried out in a qualitative descriptive way, to answer objectives one, two, and three, which were obtained from the results of interview reports and observations.. Based on the results of the study indicate that the average total cost is Rp. 10,597,544 /Harvest Period consists of a fixed fee of Rp. 70,550/Harvest Period and a variable fee of Rp. 10,526,993 // Harvest Period. The average income obtained by farmers is Rp. 86.400.000 / Harvest Period, for an income of Rp. 75,802,456/Harvest Period. Jernang plants use organic and inorganic fertilizers. Fertilizer is given in several stages, first given before or at the same time as planting, fertilizer is inserted into the planting hole at a dose of 2 kg per planting hole or NPK 100 g per planting hole. Furthermore, continued fertilizer was started after the plants were 6 months old. NPK with doses between 50-100 grams per plant which is done every 6 months. Fertilization of compost or manure is also done by placing it around the plants. Harvesting of fruit is done once every 3 months to get optimal results and the average yield of jernang is 1,080 Kg/Harvest Period. Marketing is done indirectly by delivering the jernang to the buyer's location